Brassinosteroid-Induced Transcriptional Repression and Dephosphorylation-Dependent Protein Degradation Negatively Regulate BIN2-Interacting AIF2 (a BR Signaling-Negative Regulator) bHLH Transcription Factor - Kim, Yoon; Song, Ji-Hye; Park, Seon-U; Jeong, You-Seung; Kim, Soo-Hwan (Plant and cell physiology, 2017)
Brassinosteroids (BRs) are plant polyhydroxy-steroids that play important roles in plant growth and development via extensive signal integration through direct interactions between regulatory components of different signaling pathways. Recent studies have shown that diverse helix-loop-helix/basic helix-loop-helix (HLH/bHLH) family proteins are actively involved in control of BR signaling pathways and interact with other signaling pathways. In this study, we show that ATBS1-INTERACTING FACTOR 2 (AIF2), a nuclear-localized atypical bHLH transcription factor, specifically interacts with BRASSINOSTEROID-INSENSITIVE 2 (BIN2) among other BR signaling molecules. Overexpression of AIF2 down-regulated transcript expression of growth-promoting genes, thus resulting in retardation of growth. AIF2 renders plants hyposensitive to BR-induced root growth inhibition, but shows little effects on BR-promoted hypocotyl elongation. Notably, AIF2 was dephosphorylated by BR, and the dephosphorylated AIF2 was subject to proteasome-mediated degradation. AIF2 degradation was greatly induced by BR and ABA, but relatively slightly by other hormones such as auxin, gibberellin, cytokinin and ethylene. Moreover, AIF2 transcription was significantly suppressed by a BRI1/BZR1-mediated BR signaling pathway through a direct binding of BRASSINAZOLE RESISTANT 1 (BZR1) to the BR response element (BRRE) region of the AIF2 promoter. In conclusion, our study suggests that BIN2-driven AIF2 phosphorylation could augment the BIN2/AIF2-mediated negative circuit of BR signaling pathways, and the BR-induced transcriptional repression and protein degradation negatively regulate AIF2 transcription factor, reinforcing the BZR1/BES1-mediated positive BR signaling pathway.